The formation of waste management order in urban communities under the neo endogenous development theory: Two examples from Chinese urban communities - Xue, Mengchun; Liu, Meng (Frontiers in Environmental Science, 2025)
IntroductionChina's urban community waste management (UCWM) is plagued by severe environmental pollution, resource wastage, and insufficient public participation, necessitating an urgent shift towards sustainable practices through grassroots mobilization. This study explores how urban communities can integrate external resources and endogenous dynamics to form sustainable waste management orders, guided by the Neo Endogenous Development (NED) theory.MethodsThis study collected data using the interview method and analyzed the data through NVIVO 12.0 to explore the integration of external resources and internal dynamics in forming sustainable UCWM orders in two representative Chinese urban communities in Beijing and Shanghai.ResultsThe findings reveal that technology, as an exogenous force, effectively stimulates endogenous sustainable development by aggregating subjects through platform empowerment, activating grassroots resources via data interoperability, and fostering social connections and environmental awareness. The NED framework, which integrates technology empowerment, multi-stakeholder collaboration, resource activation, and value creation, demonstrates significant potential in enhancing sustainable waste management.DiscussionThese results highlight the synergistic role of technological innovation, stakeholder collaboration, and community empowerment in achieving sustainable waste management. The study underscores the replicability of NED-based waste management models in diverse socio-economic settings. Practical policy recommendations include increased government subsidies for smart devices, legislation for waste sorting responsibilities, and technology adoption tailored to community needs.